THE IMPACT OF TV ADVERTISING TOWARDS CONSUMER BUYING BEHAVIOR IN MANADO - Mengko, Lidya P.; Pangemanan, Sifrid S.; Tumbuan, Willem J.F.A (Universitas Sam Ratulangi, 2018)
Abstract: Nowadays, the rapid developments of technology makes the internet users continue to increase time to time. It is also supported by the ease of customer accessing the internet through mobile phones, computers, and other media. This makes online purchases in Indonesia greatly improved in recent years. This increase of the users makes the right promotion by using TV advertising. The aim of this study is to analyze the impact of TV advertising towards consumer buying behavior withdrawing taking e-commerce Shopee Indonesia as its case study. This research is causal type of research which uses primary data that obtained through questionnaires and uses Ordinal Regression Analysis. The population that observed is people in Manado who have experienced using Shopee Indonesia with 80 respondents as the sample size. The result of this study shows that credibility, interactivity and informativeness have significant impacts on consumer buying behavior. In contrast to entertainment that have no significant impact on consumer buying behavior. Although the advertising that made by Shopee Indonesia can be categorized successful in introducing its products to customer. Shopee Indonesia should improve their promoting strategy through e-commerce in order to attract the customer by good TV advertising to make the customer to purchase.Keywords: consumer buying behavior, credibility, interactivity, entertainment, informativeness